Type of Occupation and Smoking Behavior: A Multinomial Analysis of Global Adults Tobacco Survey (GATS) Indonesia - Suyitno Suyitno; Widya Hary Cahyati (JURNAL INFO KESEHATAN, 2025)
Smoking remains a major public health problem in Indonesia, with occupation playing a key role in shaping smoking behavior. This study investigated how occupational type affects smoking behavior among Indonesian adults. This study was using data from the 2021 Global Adult Tobacco Survey (GATS), which included 9,155 respondents. The dependent variable was smoking behavior (daily smoker, non-daily smoker, or never smoker), and the main independent variable was occupational type. Control variables included age, gender, education level, and place of residence. Data analysis involved descriptive statistics, chi-square test, ANOVA, and multinomial logistic regression. The results showed that 25.47% of adults were daily smokers, 5.95% were non-daily smokers, and 68.57% were never smokers. Most participants were unemployed (47.67%), indoors workers (15.03%), outdoors (32.90%), or in both settings (4.40%). Bivariate analysis revealed significant associations between smoking behavior and type of occupation, gender, education, place of residence, and age. Daily smoking was more common among men, individuals with lower education, rural residents, and outdoor workers. Multivariate analysis indicated that outdoor workers were significantly more likely to smoke daily than indoor workers (OR = 1.36–1.96). Compared with unemployed individuals, those occupation indoors, outdoors, and in both environments were 1.82, 2.87, and 2.94 times more likely to smoke daily, respectively. These findings suggest that employment, especially outdoor employment, is strongly associated with daily smoking. Targeted smoking prevention programs should prioritize outdoor workers, men, rural residents, and those with lower education levels.